2006
DOI: 10.1124/mol.106.022608
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor (LXR)-β Regulation in LXRα-Deficient Mice: Implications for Therapeutic Targeting

Abstract: The nuclear receptors liver X receptor (LXR) LXR␣ and LXR␤ are differentially expressed ligand-activated transcription factors that induce genes controlling cholesterol homeostasis and lipogenesis. Synthetic ligands for both receptor subtypes activate ATP binding cassette transporter A1 (ABCA1)-mediated cholesterol metabolism, increase reverse cholesterol transport, and provide atheroprotection in mice. However, these ligands may also increase hepatic triglyceride (TG) synthesis via a sterol response element b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 41 publications
(68 reference statements)
8
104
1
1
Order By: Relevance
“…In mice lacking LXRα, but not in those lacking LXRβ, removal of cholesterol from the body is severely impaired (18,36). Conversely, systemic activation of LXR with LXR agonists reduces whole-body cholesterol levels in LXR WT mice and raises HDL levels in the plasma (40)(41)(42) confirming that in mice, LXR is the key regulator of cholesterol homeostasis in liver.…”
Section: Lxr Function In Liver Lxr In Cholesterol Homeostasismentioning
confidence: 61%
See 3 more Smart Citations
“…In mice lacking LXRα, but not in those lacking LXRβ, removal of cholesterol from the body is severely impaired (18,36). Conversely, systemic activation of LXR with LXR agonists reduces whole-body cholesterol levels in LXR WT mice and raises HDL levels in the plasma (40)(41)(42) confirming that in mice, LXR is the key regulator of cholesterol homeostasis in liver.…”
Section: Lxr Function In Liver Lxr In Cholesterol Homeostasismentioning
confidence: 61%
“…Although there is very little LXRβ expressed in hepatocytes, literature data diverge concerning the role of LXRs in liver TG accumulation. While some groups report that only LXRα is responsible for liver accumulation of TG (24), others have shown that both LXR isoforms may be responsible for liver lipogenesis (36,38). In LXRα KO mice, lipogenesis in liver is less than in WT mice.…”
Section: Lxr In Regulation Of Triglyceridesmentioning
confidence: 96%
See 2 more Smart Citations
“…LXR activation also regulates CYP7A1 transcription via LXREs. Impaired CYP7A1 levels have been reported in LXRα −/− mice, resulting in hepatic cholesterol accumulation 29) . Furthermore, activation of the CYP7A1 gene expression is induced by crosstalk between TR-β and LXR-α, thereby controlling cholesterol metabolism 30) .…”
Section: Lxrmentioning
confidence: 99%